ChemInform Abstract: BOROX Catalysis: Self‐Assembled Amino‐BOROX and Imino‐BOROX Chiral Broensted Acids in a Five‐Component Catalyst Assembly/Catalytic Asymmetric Aziridination. Issue 3 (22nd January 2013) - Gupta, Anil K.; Mukherjee, Munmun; Hu, Gang; Wulff, William D.
Abstract Treatment of amines (I) with aldehydes and diazoacetate in the presence of B(O‐Ph)3 and diol (S)‐VPO allows a highly stereo‐ and chemoselective access to cis‐substituted aziridines.